OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) PAJAK KENDARAAN BERMOTOR PADA KANTOR UPT. BAPENDA PROVINSI KALIMANTAN TIMUR WILAYAH KOTA SAMARINDA TAHUN 2016 – 2018 - Ida Rahmawati3, Vinia Tiara Aristi Titin Ruliana2 (EKONOMIA, 2021)
Optimization of Regional Original Income (PAD) Motor Vehicle Tax at the UPT office. BAPENDA of East Kalimantan Province, Kota Samarinda Region 2016 - 2018 (under the Guidance of First Advisor, Mrs. Titin Ruliana and and Second Advisor, Mrs. Ida Rahmawati).Optimization is an effort to increase the ability that is most desired among the criteria of creativity or in other words, an effort to maximize the existing resources to achieve the expected goals. The definition of Regional Original Income (PAD) is regional revenue that comes from regional taxes, the results of regional management, and other legitimate regional original revenues, which aim to provide graduation to the daetah in assisting the implementation of regional autonomy as the embodiment of the principle of being centralized.The research objective achieved is to determine the target of local tax revenue in the motor vehicle tax sector at UPT. Bapenda of East Kalimantan Province and analyzes whether the average target performance for 2016-2018 is very optimal when viewed from the percentage of realization of target revenue target PKB UPT Bapenda East Kalimantan Province.Based on the research background that has been described, a research hypothesis can be formulated which states that the level of revenue from the local tax revenue target in the Motor Vehicle Tax Sector at UPT Bapenda East Kalimantan is very optimal.The performance of the realization of local tax revenue targets through the motor vehicle tax sector at the UPT Bapenda of East Kalimantan Province in 2016-2018 is very optimal, which is above 80%.